Phenotypic and genotypic characterization of Campylobacter coli isolates from the Vietnamese poultry production network; a pilot study - Lehri, Burhan; Navoly, Georgina; Corser, Abigail; Nasher, Fauzy; Willcocks, Sam; Pham, Thi Ngoc; Wren, Brendan W.; Luu, Quynh Huong; Stabler, Richard A. (Frontiers in Industrial Microbiology, 2024)
Introduction Changing farming practices and the associated increase in the use of antibiotics are amongst the main drivers shaping the global increase of Campylobacter infections. The effects farming practices have on Campylobacter species, need to be studied at the global scale, particularly in emerging middle-income countries, where the demand for low-cost poultry meat is rising. While Campylobacter jejuni causes the majority of poultry associated diarrhoea, Campylobacter coli causes a significant amount of disease but are relatively understudied. In this study we characterised seven C. coli strains isolated from chicken faeces and chicken meat in Thai Nguyen province, Vietnam. Methods Whole Genome Sequencing and phenotypic assays (growth, motility, antimicrobial resistance testing, virulence assay) were performed to reveal the genetic relatedness and pathophysiological characteristics of the isolates. Results All isolates were resistant to ciprofloxacin and nalidixic acid but susceptible to phenicols. Three were resistant to macrolides azithromycin and erythromycin. Six isolates were classified as multi-drug resistant. All isolates had similar growth rates in laboratory culture media, while five were hyper-motile. Lethality towards a tractable host-model system, larvae of the greater wax moth Galleria mellonella, often used to determine Campylobacter virulence, was demonstrated for the first time for C. coli. Discussion Multilocus sequence typing data identified five ST’s all within the C. coli ST-828 clonal complex and were previously reported in North American (ST-829), European (ST-1586), and Asia (ST-5511) from patients suffering from gastroenteritis, emphasising the global spread of these strains. This work highlights the importance of further research into this understudied global threat.